2007
DOI: 10.1089/end.2006.0454
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Tract Dilation for Percutaneous Nephrolithotomy: Is It Justified?

Abstract: One-stage tract dilation for PCNL is a safe and effective method in almost every adult patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…The current study and previous studies by Ziaee et al [4] and Falahatkar et al [2] demonstrated lower total radiation exposure time in the access creation stage with the one-stage tact dilation method. We think this method is a suitable option for pediatric patients.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The current study and previous studies by Ziaee et al [4] and Falahatkar et al [2] demonstrated lower total radiation exposure time in the access creation stage with the one-stage tact dilation method. We think this method is a suitable option for pediatric patients.…”
Section: Discussionsupporting
confidence: 78%
“…A few studies have assessed the safety of this method for PCNL in adult patients. Ziaee et al [4] compared the efficiency and complications of tract dilation by the one-stage method in 46 patients with a history of ipsilateral flank surgery and 54 patients without such a history. They observed no statistically significant difference in hemorrhage, radiation exposure and access time between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Amirhassani et al have expressed that PNL with one-shot technique is a safe and tolerable method due to low complication rate and radiation exposure. 15 Our results for PNL with one-shot method performed in patients who had and had not had previous open surgery were similar to the results in the literature.…”
Section: Discussionmentioning
confidence: 99%